Phase 3 trials of new antiretrovirals are not representative of the global HIV epidemic - Toby Pepperrell; Andrew Hill; Michelle Moorhouse; Polly Clayden; Kaitlyn McCann; Simiso Sokhela; Celicia Serenata; Willem Daniel Francois Venter (Elsevier, 2020)
Introduction: People living with HIV (PLWH) are mainly African or Asian, the majority female. In contrast, pharmaceutical companies typically conduct phase 3 regulatory randomised controlled trials (RCTs) in high-income countries (HICs), where PLWH are mainly white males. Regulatory authorities can be conservative about including pregnant women in trials, discouraging female participation. Some adverse events occur more frequently by sex or by race because of differing pharmacokinetics. Most drugs have insufficient safety data in pregnancy and non-white people even after regulatory approval. The present study compared race and sex demographics of phase 3 RCTs of dolutegravir (DTG), bictegravir (BIC) and tenofovir alafenamide (TAF) with global HIV epidemic demography. Methods: National epidemic sizes by sex were extracted from UNAIDS 2018 data. National demographics were used to estimate prevalence by race. PLWH by national socio-economic status were calculated from World Bank data. Summary race and sex demographic data for 10 phase 3 trials of DTG (n = 7714), four of BIC (n = 2307), eight of TAF (n = 7573) and two of doravirine (DOR) (n = 1407) were extracted from ClinicalTrials.gov. Results: Black females (42%) and black males (30%) have highest prevalence globally. White males comprise 6% of PLWH. Over 60% of PLWH live in low or low-middle-income countries, 68% of whom are black and 23% Asian. Seventy-six per cent of DTG trial centres were in high-income countries (HICs) (5% global burden) and 23% in upper-middle-income countries (UMICs). DTG trials were not representative of PLWH even within the UMIC and HIC setting (49% white male vs 31% income band). White males were overrecruited by 44% to DTG, BIC, TAF and DOR trials in comparison with prevalence. Black females were underrepresented by 35%. Conclusion: Phase 3 RCT populations for new antiretrovirals comprised 51% white males, vastly disproportionate to the global HIV epidemic (6%). Females and non-white people are underrepresented. Female safety data are insufficient despite drug approval in Europe and USA. HIV trials should be located in regions representing the global epidemic with no sex-based selection. Trials should aim for at least 50% female and 50% non-white recruitment to properly provide safety information.